Transformasi Digital dan Penguatan Tata Kelola UMKM Berbasis Green Business pada Lucky Fingers Cafe - Ari Pambudi; Ida Faridah; Ikhsan Nurahman; Anggraeni Pratama Indrianto (Civiliza Publishing, 2026)
This community service program aims to support the digital transformation and strengthen business governance of Lucky Fingers Cafe as a growing micro, small, and medium enterprise (MSME) through an integrated approach based on green business principles. As the business expands in scale, customer volume, and operational complexity, challenges arise in managing business processes, financial recording, service quality, and environmental responsibility. The assistance was carried out through mentoring and training in the utilization of information systems, improvement of management practices, strengthening of simple accounting records, and recommendations for the use of environmentally friendly packaging. The methods included initial needs assessment, implementation of mentoring sessions, practical guidance, and evaluation of business practices. The results show an improvement in the partner’s understanding and application of digital tools, more structured financial management, better operational organization, and increased awareness of sustainable business practices. The adoption of green packaging is expected to enhance the business image and align the enterprise with environmentally conscious consumer trends. This program demonstrates that integrated assistance combining digitalization, governance strengthening, and sustainability can effectively support the growth and competitiveness of MSMEs.